Personality Traits and COVID-19 Vaccination Status in Slovakia: The Role of Trust in Health Institutions, and COVID-19 Pseudo-Science and Conspiracy Beliefs - Halama, Peter (Studia Psychologica, 2025)
The present study focuses on the Big Five personality traits as predictors of COVID-19 vaccination status in the population of Slovakia. The sample consisted of 1838 inhabitants of Slovakia (47% men, 53% women, mean age 45.41 years) recruited through an online panel of a research agency. Participants were administered the Big Five personality test BFI-2-S, and items regarding vaccine pseudo-science, conspiracy beliefs, and trust in medical institutions. They also reported their COVID-19 vaccination status. The results showed that after controlling for gender, age, education, and social status, agreeableness and negative emotionality predicted the vaccination status; in both cases, lower levels of the trait predicted not being vaccinated. The effect of agreeableness on vaccination status was mediated by low levels of COVID-19 pseudo-science and conspiracy beliefs and higher trust in medical institutions.